Coriander response to nitrogen fertilizer sources in different competing levels of weeds - Fatemeh Alaei; Saeideh Maleki Farahani; Hassan Habibi; Mohammad Hossein Fotokian; Mostafa Khodadadi (Heliyon, 2024)
The competition of weeds with crops and nutrient management has a significant effect on the yield and economic efficiency of a country. This study aimed to evaluate the impacts of sulfur-coated urea and common urea on the yield and fatty acid composition of three coriander genotypes (Nahavandi, Pishgam, Ethiopia) under weeded and unweeded conditions. Traits including 1000 seeds weight, fruit yield, content of oil, and composition of fatty acids were examined. Nitrogen fertilizer and weeding treatments significantly improved the weight of 1000 seeds and weeds decreased the yield of fruit. The highest fruit yield was obtained by the Ethiopia genotype in weed-free conditions. Results showed that N fertilizer increased the oil percentage of coriander fruit. Urea fertilizer resulted in the highest oil content in the Nahavandi and Pishgam genotypes under weeded plots in the first and second years, respectively. Also, petroselinic, linoleic, and palmitic acids were the major coriander fatty acid composition. Nahavandi genotype showed the highest palmitic acid. Also, urea in the weed condition led to increase the linoleic acid content in the Nahavandi genotype. Overall, results showed that N fertilizer, especially urea, improved the quality characteristics of coriander fruits.